The level of Escherichia coli contamination in foods and drinks sold at canteens campus (Faculty of Medicine Universitas Indonesia, 2011)
Background: Bacterial contamination is a common phenomenon in foods served in campus canteens and my cause physical illness which will affect academic activity. The aim of this study was to rank the level of Escherichia coli contamination in food and drink in campus canteens. Methods: Forty nine (49) foods and 24 types of drink were examined using conventional agar broth method for calculation of most probable number (MPN). The steps of the mothod were presumptive test for coliforms, fecal coliforms and E. coli, confirmes test for coliforms, fecal coli and E. coli and then completed test for E. coli. An analysis for contamination by E. coli in meals, utensils, and on the hands of the server was also undertaken. The data analyzed in percentage and rank all type of foods and drinks, also rank based on the location. Results: Almost all type of meals was contaminated. Meals with chili sauce were the most risky from the contamination of E. coli (90.15 %), then followed by dry meals (38.89%), while the wet meals were the the most unrisky meals. In drinks, the highest was lacy juice, followed by jambu (guava) juice, then Sirsak and Orange juices on the third rank, while the mango juice was the lowest contamination. Melon juice, cappucino and fruit-coctail did not have E. coli contamination. Conclusion: The contamination in the top three rank of contamination could be from the utensils used and foodhandler. (Med J Indones 2011; 20:66-70) Keywords: campus, canteen, drink, Escherichia coli, food